Lr21 diversity unveils footprints of wheat evolution and its new role in broad‐spectrum leaf rust resistance. (28th July 2021) - Naz, Ali A.; Bungartz, Annemarie; Serfling, Albrecht; Kamruzzaman, Mohammad; Schneider, Michael; Wulff, Brande B. H.; Pillen, Klaus; Ballvora, Agim; Oerke, Erich‐Christian; Ordon, Frank; Léon, Jens
Abstract: Aegilops tauschii, the progenitor of the wheat D genome, contains extensive diversity for biotic and abiotic resistance. Lr21 is a leaf rust resistance gene, which did not enter the initial gene flow from Ae. tauschii into hexaploid wheat due to restrictive hybridization events. Here, we used population genetics and high‐resolution comparative genomics to study evolutionary and functional divergence of Lr21 in diploid and hexaploid wheats. Population genetics identified the original Lr21, lr21‐1 and lr21‐2 alleles and their evolutionary history among Ae. tauschii accessions. Comparative genetics of Lr21 variants between Ae. tauschii and cultivated genotypes suggested at least two independent polyploidization events in bread wheat evolution. Further, a recent re‐birth of a unique Lr21‐tbk allele and its neofunctionalization was discovered in the hexaploid wheat cv. Tobak. Altogether, four independent alleles were investigated and validated for leaf rust resistance in diploid, synthetic hexaploid and cultivated wheat backgrounds. Besides seedling resistance, we uncover a new role of the Lr21 gene in conferring an adult plant field resistance. Seedling and adult plant resistance turned out to be correlated with developmentally dependent variation in Lr21 expression. Our results contribute to understand Lr21 evolution and its role in establishing a broad‐spectrum leaf rust resistance in wheat. Abstract : The present study uncovers evolutionary divergence of Lr21 in Aegilops tauschii accessions and its transfer to hexaploid wheat as well as its new role in conferring broad‐spectrum resistance against leaf rust in bread wheat.